Finite element method for the study of air-cushion tracked vehicle-terrain interaction - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Shaari, Norazean; Arif, Mohd; Iqbal, A.K.M.P.; Hassan, Khairul (2010)
This paper presents the numerical analysis by means of the finite element method (FEM) to perform experiment findings of a model tracked vehicle-terrain interaction. A static analysis was performed with three different vehicle loading conditions of 1.96 kN, 2.45 kN, and 2.94 kN, respectively, to obtain the performance of the track frame design. Finite element mesh and its deformed pattern and the distribution of vertical stress were obtained in swamp terrain beneath a rigid chassis frame and sprocket wheel with a diameter of 200 mm and vertical load of 1.96 kN, 2.45 kN, and 2.94 kN, respectively, at 13.6% slippage. Based on the predicted displacements of the nodal points, the deformation of the element was determined. The result shows that the critical point of stress occurred at the opening of chassis which is in contact with the track-terrain interface and was found as maximum at 33.70 MPa and minimum at 0.211e-3 MPa. At the deflection on the plate where the engine and alternator are located, the stresses were found between 3.744 MPa and 7.488 MPa. It was also observed that lowest amount of displacement were occurred at the rear part of the side frames where the rear sprockets are located with the value of 4.82 mm in the negative x-direction.